Performance measurement analysis : Shariah-compliant vs. Non Shariah-compliant securities / Mohd Allif Anwar and Norli Ali - Abu Bakar, Mohd Allif Anwar; Ali, Norli (Faculty of Accountancy & Accounting Research Institute (ARI), 2014)
Using the sample of 107 shariah-compliant and non shariah-compliant securities in Malaysia from January 1990 to December 2011, we examine their performances by applying the performance measure of Jensen Alpha Index and Treynor Index. The sample period is divided into four segments of pre AFC (Asian Financial Crisis), during AFC, post AFC and Subprime Mortgage Crisis. Our results showed that the performance of shariah compliant securities tend to be indifferent with non shariah-compliant securities. However, the performance of both portfolios is significantly different between the four segments of pre AFC, during AFC, post AFC and Subprime Mortgage Crisis. One important portfolio implication from this study is that the market players are able to plan ahead in their investment and portfolio diversification especially during economic downturns.